2016
DOI: 10.3892/ol.2016.5290
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between miR-7 expression and treatment outcomes with gefitinib in non-small cell lung cancer

Abstract: The aim of the present study was to assess the effects of gefitinib chemotherapy on the serum levels of miR-7 in patients with non-small cell lung cancer (NSCLC). A total of 126 patients were enrolled in the present study (stage I–II, n=54 and stage III–IV, n=72). Patients with stage I–II NSCLC underwent surgery in combination with gefitinib chemotherapy, whereas only gefitinib chemotherapy was administered to patients with stage III–IV disease. Serum levels of miR-7 before and after treatment were measured wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In this study, we explore the effects of SOX21-AS1 on CC cells and found that SOX21-AS1 served as endogenous miRNA sponges to bind to miR-7. Previously, the biological function of SOX21-AS1 had been investigated in several tumors, including breast cancer, non-small cell lung cancer and CC (Hao et al, 2015;Mou et al, 2016;Raychaudhuri et al, 2017). Importantly, in CC, miR-7 was reported to serve as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we explore the effects of SOX21-AS1 on CC cells and found that SOX21-AS1 served as endogenous miRNA sponges to bind to miR-7. Previously, the biological function of SOX21-AS1 had been investigated in several tumors, including breast cancer, non-small cell lung cancer and CC (Hao et al, 2015;Mou et al, 2016;Raychaudhuri et al, 2017). Importantly, in CC, miR-7 was reported to serve as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…ISH staining of TMA sections was scored independently evaluated under the light microscope at a magnification of × 200 by two independent pathologists Qiuyuan Wen and Yuting Zhan who blinded to the clinical data. The scores were based on the staining intensity and extent of staining 40 . Staining intensity for miR-4634 was scored as 0 (negative), 1 (weak), 2 (moderate), and 3 (strong) and staining extent was scored as 0 (0%), 1 (1–25%), 2 (26–50%), 3 (51–75%), and 4 (76–100%).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in vivo experiments showed that miR-134 suppressed tumor growth of A549 xenograft in nude mice [36,55,56,124]. Immunoblotting showed that EGFR protein levels were also significantly downregulated with miR-7 downregulation [82,[125][126][127][128].…”
Section: Effect Of Egfr Activation On Mirna Expressionmentioning
confidence: 97%